2005
DOI: 10.1103/physrevlett.94.183902
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mesoscopic Magnetism in Photonic Crystals

Abstract: We provide a rigorous theoretical basis for the artificial magnetic activity of meta-materials near resonances. Our approach is a renormalization-based scheme that authorises a completely general theory. The major result is an explicit expression of the effective permeability, in terms of resonant frequencies. The theoretical results are checked numerically and we give applications of our theory to Left-Handed Media and to the solution of the Pokrovski-Efros paradox.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 21 publications
1
74
0
Order By: Relevance
“…It follows that the induced magnetic activity cannot result simply from the superposition of independent Helmholtz micro-resonators as depicted in [12]. Interactions between the inclusions and the substrate have to be well understood.…”
Section: Introduction and Description Of The Modelmentioning
confidence: 99%
“…It follows that the induced magnetic activity cannot result simply from the superposition of independent Helmholtz micro-resonators as depicted in [12]. Interactions between the inclusions and the substrate have to be well understood.…”
Section: Introduction and Description Of The Modelmentioning
confidence: 99%
“…The cloaking device is usually given by coefficients with extreme values, large or small, or by negative coefficients in some part of the domain. In this sense, many ideas for cloaking can be considered as realizable only since the invention of negative index metamaterials [22], for which mathematical justifications can be found for instance in [7,3,13,4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have for example noticed a correlation between the resonances of single dielectric objects and the opening of photonic band gaps (PBGs) in arrays of them [15,16]. In the context of MMs, arrays of dielectric rods in p-polarized light (magnetic field parallel to the axis of the rods) have been shown to possess an effective, dispersive, magnetic permeability [17,18]. Interestingly, it has further been suggested that dielectric rods in s-polarized light (electric field parallel to the axis of the rods) could exhibit both electric and magnetic dipole resonances, and thus, possibly constitute a so-called left-handed (LH) medium with simultaneously negative permittivity and permeability [11,12].…”
mentioning
confidence: 99%